PENDIDIKAN POLITIK DAN PEMBENTUKAN KELOMPOK PENGAWAS DANA DESA - Alfian, Faqih; akbar, taufik (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
Education is one means for transferring knowledge. With a variety of media used, it is expected to be able to provide the expected information. Political education is one of them, with the hope that people understand and understand what is meant by politics. Especially in rural communities where the tendency to have minimal information about politics. In this activity, political education uses the andragogy method, where learning is specifically for adults. Invite the community to play an active role in the problems that exist. Focus Group Discussion is one vehicle for community involvement, they can express their opinions. The main target in this activity is the youth group. The results of service are: 1. The implementation of